Full-disc Ca ii K observations—A window to past solar magnetism - Chatzistergos, Theodosios; Krivova, Natalie A.; Ermolli, Ilaria (Frontiers in Astronomy and Space Sciences, 2022)
Full-disc observations of the Sun in the Ca II K line provide one of the longest collections of solar data. First such observations were made in 1892 and since then various sites around the world have carried out regular observations, with Kodaikanal, Meudon, Mt Wilson, and Coimbra being some of the more prominent ones. By now, Ca II K observations from over 40 different sites allow an almost complete daily coverage of the last century. Ca II K images provide direct information on plage and network regions on the Sun and, through their connection to solar surface magnetic field, offer an excellent opportunity to study solar magnetism over more than a century. This makes them also extremely important, among others, for solar irradiance reconstructions and studies of the solar influence on Earth's climate. However, these data also suffer from numerous issues, which for a long time has hampered their analysis. Without properly addressing these issues, Ca II K data cannot be used to their full potential. Here, we first provide an overview of the currently known Ca II K archives and sources of the inhomogeneities in the data, before discussing existing processing techniques, followed by a recap of the main results derived with such data so far.